Educational Games: Enhancing Father-Child Attachment in Supporting Children's Self-Disclosure and Academic Achievement - Setriani; Meilia Ishar; Daffa Tiara Kurnia Prastiwi (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2025)
This study aims to examine the effectiveness of the educational game